Subducted oceanic relief locks the shallow megathrust in central Ecuador. Issue 5 (13th May 2017) - Collot, Jean‐Yves; Sanclemente, Eddy; Nocquet, Jean‐Mathieu; Leprêtre, Angélique; Ribodetti, Alessandra; Jarrin, Paul; Chlieh, Mohamed; Graindorge, David; Charvis, Philippe
Abstract: Whether subducted oceanic reliefs such as seamounts promote seismic rupture or aseismic slip remains controversial. Here we use swath bathymetry, prestack depth‐migrated multichannel seismic reflection lines, and wide‐angle seismic data collected across the central Ecuador subduction segment to reveal a broad 55 km × 50 km, 1.5–2.0 km high, low height‐to‐width ratio, multipeaked, sediment‐bare, shallow subducted oceanic relief. Owing to La Plata Island and the coastline being located, respectively, 35 km and 50–60 km from the trench, GPS measurements allow us to demonstrate that the subducted oceanic relief spatially correlates to a shallow, 80 km × 55 km locked interplate asperity within a dominantly creeping subduction segment. The oceanic relief geometrical anomaly together with its highly jagged topography, the absence of a subduction channel, and a stiff erosive oceanic margin are found to be long‐term geological characteristics associated with the shallow locking of the megathrust. Although the size and level of locking observed at the subducted relief scale could produce an M w >7+ event, no large earthquakes are known to have happened for several centuries. On the contrary, frequent slow slip events have been recorded since 2010 within the locked patch, and regular seismic swarms have occurred in this area during the last 40 years. These transient processes, together with the rough subducted oceanic topography, suggest that interplate friction might actually be heterogeneous within the locked patch. Additionally, we find that the subducted relief undergoes internal shearing and produces a permanent flexural bulge of the margin, which uplifted La Plata Island. Plain Language Summary: Subducted seamounts play an important but still uncertain role in earthquake rupture processes, as seamounts are considered to subduct either aseismically or seismically. We use marine geophysical data across the central Ecuador convergent margin to reveal a broad 55 km × 50 km, 1.5–2.0 km high, shallow subducted oceanic relief of the Carnegie Ridge. New GPS measurements collected on La Plata Island and along the Ecuador coast allow us to demonstrate that the subducted oceanic relief spatially correlates to a shallow, 80 km × 55 km locked interplate asperity within a dominantly creeping subduction segment. The oceanic relief geometrical anomaly together with its rough topography and the stiff oceanic Ecuador margin are found to be long‐term geological characteristics associated with the shallow locking of the plate interface. Although the size and level of locking observed at the subducted relief scale could produce an M w >7+ event, no large earthquake but frequent slow slip events and associated seismic swarms occurred within the locked patch. These transient processes together with the rough subducted oceanic topography support the view of a heterogeneous interplate frictional pattern within the locked patch. On a regional scale, the subduction of the oceanic relief has deformed the Ecuador margin and uplifted La Plata Island. Key Points: Seismic imaging and geodetic data show a shallow subducted oceanic relief to lock the plate interface The jagged oceanic relief topography hosts regular slow slip events and seismic swarms occurring within the locked patch The subducted oceanic relief undergoes internal shearing and produces margin deformation including La Plata Island uplift